FROM HISTORY TO PRACTICE OF INTRODUCING COMPLEMENTARY FEEDINGS TO HEALTHY CHILDREN IN THE FIRST YEAR OF LIFE IN PEDIATRIC SITES - Татьяна Николаевна Елкина; Екатерина Александровна Суровикина; Ольга Александровна Грибанова; Юлия Анатольевна Татаренко; Маргарита Геннадьевна Лиханова (The Publishing House Medicine and Enlightenment, 2024)
The aim of the research - study of the nutritional characteristics of young children and their compliance with current national recommendations. Materials and methods. 100 parents of healthy children aged 18-36 months were interviewed using a specially designed questionnaire, which included answers to questions related to the peculiarities of feeding a child in the first year of life, as well as actual nutrition at the time of the questionnaire. The survey was carried out at the pediatric sites of the city polyclinics of Novosibirsk. Among the children studied, 56 % were boys and 44 % were girls. Results. Complementary foods began to be given at 4 months 45 % of parents, at 5 months - 30 %, in 6 - 23 %, later 6 months - 2 %. Porridge was introduced as the first complementary food by 32 %; vegetables 47 %, fruits 21 %, of which juice 38 %, puree 62 %. The first porridge was more often gluten-free (77 %), buckwheat (65 %). Meat complementary foods were introduced at 6 months by 37 %, later by 59 %, and earlier by 4 %. Cottage cheese earlier than 6 months was introduced in 4 %, in 6-7 months. - 24 %, 8 months - 42 %, the rest from 9 to 12 months. 65 % of children started receiving kefir/yogurt at 8 months or later; 35 % of parents gave these products before the prescribed period. Salt and sugar were given to children under 1 year of age by 35 % of respondents. 38 % of the children received only home-made complementary foods, of which 5 % were from the common table. The rest used wholly or partially specialized children's products. All parents received information about baby food from different sources at the same time: 80 % from the local pediatrician, 45 % including from the Internet, 33 % from relatives. 98 % of those surveyed believed that their children were eating healthily. 2 % noted that the child was eating incorrectly. Conclusion. The timing of the introduction of the first complementary foods corresponded to national recommendations for 79 % of respondents. The sequence of introduction of complementary foods was disrupted, mainly due to the choice of fruits as the first complementary food, starting with gluten-containing porridge, and too early introduction of unadapted dairy products. Ignoring and underestimating the nutritional value of specialized industrial children's food products has been revealed. Refusals to eat older than a year were recorded in 42 % of respondents.